DAMPAK BUDAYA ORGANISASI TERHADAP IMPLEMENTASI PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA DI UNIVERSITAS MUHAMMADIYAH SINJAI - Suardi Mukhlis; Muhlis Hajar Adiputra; Abdul Ganie Gaffar; Muhammad Suyuti (Program Studi Administrasi Publik, 2023)
The purpose of this independent research is to find out how the impact of organizational culture on the implementation of the independent campus independent learning program (MBKM) at the University of Muhammadiyah Sinjai (campus teaching case study) The type of research used is a qualititative method. Primary data was obtained though observation and interviews, while secondary data was obtained through documentation studies and literatute studies. The resutls showed that there was no impact given to students who attended the teaching campus in terms of accelerated study, buy for indicators to add insight, the use of practical learning media and te presentation offacilities and infrastructure have been felt by students, lectures and universities. Impact of organizational culture is innovation and risk taking, attention to detail, outcome orientation, and team orientation. The supporting fakctor for the implementation of the teaching campus are student interest, supporting from university, financing for MBKM program activies by the Ministry, and the experince prosessed by student. Meanwhile, the barrier factor for the theaching campus is the lack of facilities and infrastructure at the University of Muhammadiyah Sinjai, as well as when the lecture schedule and the teaching campus activitiies coincide.